An investigation of willingness to buy generic prescription medicines in Australia - Liang, Johan; Phau, Ian (School of Marketing, Curtin Business School, 2010)
This paper investigates consumer perception on prescription generic medicines (PGM) in Australia. Specifically, it examines how consumer concern and consumer knowledge about counterfeit medicines influence attitudes towards generic prescription medicine and willingness to pay more for branded prescription medicines. Data were collected using mail surveys to reach mature age population and 281 usable responses were used for analysis. The consumer concern was found to be significant predictor of attitude and willingness to pay more for branded prescription medicines but consumer knowledge is an insignificant predictor. Implications of the study and the corresponding recommendations are presented and discussed.